The highlander's english bride ebook - Kelly, Vanessa (Clan Kendrick, 2020)
In this dazzling new novel from bestselling author Vanessa Kelly, the wildest member of Clan Kendrick has found his purpose as a government agent. Now he must also meet his match . . . Lady Sabrina Bell has never been so embarrassed in her life. Not only did her new suitor fail to appear for their morning rendezvous in Hyde Park, but a thief pushed her into the Serpentine. Being rescued by a burly Highlander just adds to her humiliation. Nor is he content with rescuing her just once. Even when Sabrina travels to Edinburgh as part of King George's entourage, Graeme Kendrick is there, interfering, exasperating, and so very tempting . . . Once notorious for being the most unruly Kendrick brother, Graeme now runs dangerous missions for the King's spymaster. Yet nothing has prepared him for Sabrina. The only child of a wealthy earl, and the pampered goddaughter of the king himself, she is stubborn, impetuous, and far too good for him. He doesn't deserve her, but he can protect her and then send her safely back home. But the bonny Sassenach has her own ideas—and a plan for seduction that no red-blooded Highlander could resist . . .